FREEZE-DRYING KINETICS APPROACH OF SOLUBLE COFFEE. MASS TRANSFER PARAMETERS ESTIMATION - MICLĂUŞ, Vasile; DRĂGAN, Simion; (MICLĂUȘ), Adina GHIRIŞAN (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The present paper presents the freeze-drying kinetics of soluble coffee in order to determine the mass transfer parameters. Several semi-theoretical and empirical models were used to find the best fit to the experimental data. The applied models were compared using the coefficient of determination (R2), the mean relative percent error (P), the root mean square error (RMSE) and the reduced chi-square (c2). The Midilli model was found to fit better to the experimental freeze-drying data comparative to other models. The Fick’s second law was employed to determine the effective diffusion coefficient (Deff).